Pernikahan Suami Dalam Masa Iddah Istri Perspektif Maslahah Almursalah Dalam Surat Edaran Nomor: P-005/Dj.Iii/Hk.00.7/10/2021 - Siregar, Revita Mala; Siregar, Sampurna; Hsb, Putra Halomoan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
AbstractMarriages sometimes do not run smoothly and experience breakdowns, giving rise to divorce which causes a period of iddah. The aim of this research is to find out how the husband's marriage during the wife's iddah period is from the maslahah almurlah perspective in Circular Letter Number: P-005/Dj.Iii/Hk.00.7/10/2021. This research uses a normative juridical approach. So from several points stated in the circular letter Circular Number: P-005/Dj.III/Hk.00.7/10/2021 Concerning Husband's Marriage During the Wife's Iddah Period, it explains that if a husband wants to remarry another woman while the wife is divorced from him and still undergoing the iddah period according to his circumstances, then the husband must wait for his wife's iddah period to finish first. Because there are still obligations that the husband must carry out towards his wife who is still undergoing her iddah period. Advising men not to marry during the wife's iddah period is in line with the principles of maslahah murlah, where the principles of maslahah murlah are actions that contain good or useful values, as well as maintaining the objectives of the Shari'a which are limited by several limits and is not applied to things caused by human passions or desires alone. Apart from the iddah period being an opportunity to return again to rebuild the household, then maslahah murlah in enacting the law must maintain the objectives of the syara', namely maintaining religion, soul, mind, offspring and property.Keywords: Marriage, Iddah, Maslahah Almurlah.